2015
DOI: 10.1039/c4dt03362k
|View full text |Cite
|
Sign up to set email alerts
|

A study on the formation of the nitro radical anion by ornidazole and its significant decrease in a structurally characterized binuclear Cu(II)-complex: impact in biology

Abstract: An acetate-bridged binuclear Cu((II)) complex of the antiparasitic drug ornidazole was synthesized and characterized by different techniques. Single crystal X-ray diffraction revealed that the complex had a paddle wheel structure. Enzymatic assay experiments performed under anaerobic conditions on ornidazole and its Cu((II))-complex using xanthine oxidase as a model nitro-reductase showed that complex formation is able to cause a significant decrease in the reduction of the nitro group on the imidazole ring. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 35 publications
0
35
0
Order By: Relevance
“…[39][40][41][42] The titration data from cyclic voltammetry was fitted to Eq. 10 and 11 provide values for K d (= 1/K app ) using non-linear curve fit analysis.…”
Section: Electrochemistry On Purpurinmentioning
confidence: 99%
“…[39][40][41][42] The titration data from cyclic voltammetry was fitted to Eq. 10 and 11 provide values for K d (= 1/K app ) using non-linear curve fit analysis.…”
Section: Electrochemistry On Purpurinmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Their efficacy is attributed to the generation of the nitro-radical anion (R-NO 2 c À ). [1][2][3][4][5][6][7][8][9][10] In order to tackle infections caused by parasites, these molecules are rst reduced by the enzyme pyruvate ferredoxin oxidoreductase (PFOR) that acts as an electron sink. 9,10 Reduction of the nitro group prepares them for entry into cells by passive diffusion, creating a favorable concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
“…R-NO 2 c À binds to DNA, disrupting or breaking strands, leading to cell death. 9, 10 As radiosensitizers, they interact with the radicals formed on DNA following the interaction of the latter with the products of the radiolysis of water, forming R-NO 2 c À , which thereaer enhances strand unwinding or strand breaks. [6][7][8] Unfortunately, the same R-NO 2 c À ion is associated with the neurotoxic side effects, particularly when there is prolonged use of such molecules.…”
Section: Introductionmentioning
confidence: 99%
“…3,1115 Therefore, it is necessary to strike a balance between therapeutic efficacy and toxic side effects with regard to the generation of these reactive intermediates. 16,17 Research has revealed that metal complexes of anthracyclines modulate the formation of semiquinone that helps to control cardiotoxicity. 1820 However, in controlling the formation of semiquinone through complex formation in an attempt to check cardiotoxicity, efficacy of the molecule is often compromised.…”
Section: Introductionmentioning
confidence: 99%